Information Retrieval and Mining in Distributed Environments - Soro, Alessandro; Vargiu, Eloisa; Armano, Giuliano; Paddeu, Gavino; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
At DART'09, held in conjunction with the 2009 IEEE/WIC/ACM International Conference on Web Intelligence (WI 2009) and Intelligent Agent Technology (IAT 2009) in Milan (Italy), practitioners and researchers working on pervasive and intelligent access to web services and distributed information retrieval met to compare their work ad insights in such fascinating topics. Extended and revised versions of their papers, together with selected and invited original contributions, are collected in this book. Topics covered are those that emerged at DART'09 as the most intriguing and challenging: (i) community oriented tools and techniques as infrastructure of the Web 2.0; (ii) agent technology applied to virtual world scenarios; (iii) context aware information retrieval; (iv) content based information retrieval; and (v) industrial applications of information retrieval. Every chapter, before discussing in depth the specific topic, presents a comprehensive review of related work and state of the art, in the hope of this volume to be of use in the years to come, to both researchers and students.
State-of-the-Art in Group Recommendation and New Approaches for Automatic Identification of Groups.-Reputation-based Trust Disffusion in Complex Socio-Economic Networks.-From Unstructured Web Knowledge to Plan Descriptions -- Semantic Desktop: a Common Gate on Local and Distributed Indexed Resources -- An Agent-Oriented Architecture for Researcher Proling and Association using Semantic Web Technologies -- Integrating Peer-to-Peer and Multi-Agent Technologies for the Realization of Content Sharing Applications -- Intelligent Advisor Agents in Distributed Environments -- Agent-based Search and Retrieval in Virtual World Environments -- Contextual Data Management and Retrieval: a Self-organized Approach -- A Relational Approach to Sensor Network Data Mining -- Content-based retrieval of distributed multimedia conversational data -- Multimodal Aggregation and Recommendation Technologies Applied to Informative Content Distribution and Retrieval -- Using a network of scalable ontologies for intelligent indexing and retrieval of visual content -- Integrating Sense discrimination in a Semantic Information Retrieval System -- Intelligent Information Processing in Smart Grids and Consumption Dynamics.
Electronic reproduction.
Keywords: Information retrieval; Data mining; Electronic data processing -- Distributed processing; Electronic book